Cost-effectiveness of interventions to improve hand hygiene in healthcare workers in middle-income hospital settings: a model-based analysis. Issue 2 (October 2018) - Luangasanatip, N.; Hongsuwan, M.; Lubell, Y.; Limmathurotsakul, D.; Srisamang, P.; Day, N.P.J.; Graves, N.; Cooper, B.S.
Summary: Background: Multi-modal interventions are effective in increasing hand hygiene (HH) compliance among healthcare workers, but it is not known whether such interventions are cost-effective outside high-income countries. Aim: To evaluate the cost-effectiveness of multi-modal hospital interventions to improve HH compliance in a middle-income country. Methods: Using a conservative approach, a model was developed to determine whether reductions in meticillin-resistant Staphylococcus aureus bloodstream infections (MRSA-BSIs) alone would make HH interventions cost-effective in intensive care units (ICUs). Transmission dynamic and decision analytic models were combined to determine the expected impact of HH interventions on MRSA-BSI incidence and evaluate their cost-effectiveness. A series of sensitivity analyses and hypothetical scenarios making different assumptions about transmissibility were explored to generalize the findings. Findings: Interventions increasing HH compliance from a 10% baseline to ≥20% are likely to be cost-effective solely through reduced MRSA-BSI. Increasing compliance from 10% to 40% was estimated to cost US2515 per 10, 000 bed-days with 3.8 quality-adjusted life-years (QALYs) gained in a paediatric ICU (PICU) and US1743 per 10, 000 bed-days with 3.7 QALYs gained in an adult ICU. If baseline compliance is not >20%, the intervention is always cost-effective even with only a 10% compliance improvement. Conclusion: Effective multi-modal HH interventions are likely to be cost-effective due to preventing MRSA-BSI alone in ICU settings in middle-income countries where baseline compliance is typically low. Where compliance is higher, the cost-effectiveness of interventions to improve it further will depend on the impact on hospital-acquired infections other than MRSA-BSI.